Post-flood forensic analysis on small urban catchment using one dimensional system modelling - Ting, Sie Chun (Universiti Malaysia Sarawak, (UNIMAS), 2011)
A 0.47 km2 of residential houses in Sungai Mr;rah (SM) in the Sibu Town of Sarawak State is located within the Seduan River basin, which is a flood-prone area with relatively flat and typicaJly low-lying floodplain. Poor maintenance, severe conditions and water logging in the current drainage system have causes flooding with addition to water-logged soil-peat. The Wallingford Software modelInfoWorks Collection System (CS), coupled with its embedded Geographic Information System (GIS) applications, is one approach that used to identify the causes of inundation, and to improve performance of the 16 km-drainage system. ) Results show that flooding in SM area is triggered by tidal influences from the Seduan River. Some part of the drainage system in SM area failed to manoeuvre the flood water using the current existing drainage facilities. Flood mitigation in SM area is part of the Sibu Town urban water management system, which a proposed 3.7 m LSD high levee will be constructed along the Seduan River to protect the residential area from tidal impact. Tidal gates are also provided to overcome the internal drainage problems. The hydrodynamic modeling has shown its capability in identifying the effectiveness of the levee in Sungai Merah area. From this research, it is found that the levee constructed is satisfactory to prevent deluge in SM area for 20 years ARI. The simulated model is useful for the integrated assessment of flood conditions in SM area, for cost-benefit a:)sessment and risk-based design of flood protection measures and hence, it is as a decision support tool for flood risk management.